SCIENTIFIC AND THEORETICAL ASPECTS OF KHORAZM CEREMONIAL FOLKLORE (TAMADDUN NURI JURNALI, 2024)
This article deals with Khorezm ritual folklore, poetic symbols related to the wedding ceremony. Also, symbols used in songs related to children are firstly related to the concept of children, childlessness, concepts of children are analyzed separately. In particular, it was mentioned that the symbols “olma” and “nor” have other meanings.